1985
DOI: 10.1038/clpt.1985.117
|View full text |Cite
|
Sign up to set email alerts
|

Antipyrine clearance in pneumonia

Abstract: Antipyrine clearance was estimated by a one-sample technique in 14 patients with acute fever and clinical pneumonia. Antipyrine clearance during the acute illness was 31.4 +/- 7.6 ml/min (X +/- SD). Fourteen and 28 days later during convalescence, clearance values were higher (47.8 +/- 18.9 and 49.2 +/- 15.0 ml/min, respectively). We conclude that microsomal hepatic drug metabolism in adults is impaired during pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…It means that enzyme activities per unit liver volume are not lowered in old age. However, morbidities and even a subtle frailty, which is accompanied by infections that are known to impair enzyme activities of Phase I reactions (Au et al 1985, Sonne et al 1985, and (protein) malnutrition, which is known to lower activities of Phase II reactions such as GST, can lower these liver functions considerably in the elderly (Anderson et al 1982), as has been clearly shown for actaminophen by the UK group (Wynne et al 1990). …”
Section: What Really Declines With Age?mentioning
confidence: 98%
“…It means that enzyme activities per unit liver volume are not lowered in old age. However, morbidities and even a subtle frailty, which is accompanied by infections that are known to impair enzyme activities of Phase I reactions (Au et al 1985, Sonne et al 1985, and (protein) malnutrition, which is known to lower activities of Phase II reactions such as GST, can lower these liver functions considerably in the elderly (Anderson et al 1982), as has been clearly shown for actaminophen by the UK group (Wynne et al 1990). …”
Section: What Really Declines With Age?mentioning
confidence: 98%
“…Inflammation has been observed clinically to reduce P450-related hepatic drug metabolism (Renton et al, 1980;Sonne et al, 1985). In human and animal experimental systems, we and others have demonstrated a significant decrease in hepatic P450 activity following induction of the acute phase response (APR) by the administration of bacterial endotoxin (LPS) (Shedlofsky et al, 1994(Shedlofsky et al, , 1997Sewer et al, 1996;Roe et al, 1998;Warren et al, 1999Warren et al, , 2001.…”
mentioning
confidence: 99%
“…Actually, numerous reports have documented that influenza infections reduce the rate of biotransformation of theophylline and other drugs (Cheng and Morgan, 2001;Renton, 2001). Moreover, bacterial respiratory infections, as well as chronic obstructive lung disease, reduce the ability of the organism to clear xenobiotics (Sonne et al, 1985). Other causes of inflammation, such as elective surgery, reduce the activity of CYP3A4 (Haas et al, 2003).…”
mentioning
confidence: 99%